Interplay Between Electrophoretic Mobility and Intrinsic Viscosity of Polypeptide Chains - Deiber, Julio Alcides (2012)
The present work is motivated specifically by the need to find a simple interplay between experimental values of electrophoreticmobility and intrinsic viscosity (IV) of polypeptides. The connection between these two properties, as they are evaluated experimentally in a formulated dilute solution,may provide relevant information concerning the physicochemical characterization and separation of electrically charged chains such as polypeptides. Based on this aspect, a study on the relation between the effective electrophoretic mobility and the IV of the following globular proteins is carried out: bovine carbonic anhydrase, staphylococcal nuclease, human carbonic anhydrase, lysozyme, human serum albumin. The basic interpretation of the IV through polypeptide chain conformations involves two unknowns: one is the Flory characteristic ratio involving short-range intramolecular interactions and the other is the Mark–Houwink exponent associated with large-range intramolecular interactions. Here, it will be shown via basic and well-established electrokinetic theories and scaling concepts that the IV and global chain flexibility of polypeptides in dilute solutions may be estimated from capillary zone electrophoresis, in addition to classical transport properties. The polypeptide local chain flexibility may change due to electrostatic interactions among closer chain ionizing groups and the hindrance effect of their associated structural water.